Analisis kerusakan daun dan buah kelapa akibat serangan belalang Sexava - F. X. Wagiman; Meldy L.A. Hosang; Fredy Lala (Perhimpunan Entomologi Indonesia, 2019)
Sexava, the long-horned grasshopper, is an important pest of the coconut palm that destroys leaves and fruits. Study on analysis of damage to leaves and fruits of coconut palms due to being attacked by Sexava was aimed to determine the mechanism of the damage. Visual in situ observations were carried out in Salibabu Island, Talaud Islands Regency, North Sulawesi Province, while histological and chemical analyses of attacked young fruits and observation of symptoms of the secondary disease were carried out in the laboratory. The results showed that the process of damage to coconut-palm leaves and fruits due to bitten by the Sexava occurs mechanically. Phytotoxic symptoms due to bites of the long-horned grasshopper and symptoms of the secondary disease were not observed. Fruit tissue with a thickness of several millimeters appears to dry out and die while the tissue near the wound appears normal. Reduced sugar levels, cellulose, and lignin, between healthy fruit tissues (1.22%, 2.72%, 5.66%) and those attacked (1.22%, 2.85%, 4.84%) were relatively the same. The attacked young-fruits will fall out while attacked fruits on bunches more than 3 months old still keep to grow and develop until ripe.